Existing Study and Technical Recommendations for National Roads in Ambon City - Christina Siwalette; Lenora Leuhery; Hamkah Hamkah (Journal of Applied Civil Engineering and Infrastructure Technology, 2020)
The national road in Ambon City connects Pattimura Airport with Yos Sudarso Port having double access with parallel road conditions. Some road segments are not continuous like Jalan A.M. Sangadji and Jalan Rijali, have two lanes but are still one-way. This article aims to examine the capacity of the two existing national road segments in Ambon City based on the condition of each road segment according to the LHR, side barriers and continuous road requirements. The study was carried out in a structured and systematic manner according to the scientific stages using data from field observations and the latest secondary data from data sources in the BPJN XVI Ambon work unit covering Segment I (Down Road) and Segment II (Up Road). The results of the study were selected three alternative national road access, namely: First Alternative, using segment I national road access with recommendations for Reclamation of Mardika Beach, connecting 6 roads each: Jaalan Yos Sudarso, Jalan Pala, Jalan Pantai Mardika, Jalan Pantai Batu Merah, Jalan Ongko Liong, and Jalan Sultan Hasanuddin. The Second Alternative, using Segment II national road access with recommendations for Flyover Development, connecting 6 roads each: Jalan Pelabuhan, Jalan A.M. Sangadji, Jalan Diponegoro, Jalan Ahmad Yani, Jalan Rijali, and Jalan Jenderal Sudirman. The Third Alternative, using parallel national road access between Segment I and Segment II for current conditions, with recommendations on traffic engineering and handling of several road sections to be continuous.